Few-boson tunneling in a double well with spatially modulated interaction - Chatterjee, Budhaditya; Brouzos, Ioannis; Zöllner, Sascha; Schmelcher, Peter (Physical review. A, Atomic, molecular, and optical physics, 2010)
We study few-boson tunneling in a one-dimensional double well with a spatially modulated interaction. The dynamics changes from Rabi oscillations in the noninteracting case to a highly suppressed tunneling for intermediate coupling strengths followed by a reappearance near the fermionization limit. With extreme interaction inhomogeneity in the regime of strong correlations, we observe tunneling between the higher bands. The dynamics is explained on the basis of the few-body spectrum and stationary eigenstates. For a higher number of particles N⩾3, it is shown that the inhomogeneity of the interaction can be tuned to generate tunneling resonances. Finally, a tilted double well and its interplay with the interaction asymmetry are discussed.
Gesehen am 17.02.2023